Perfil comportamental e motivacional de jovens praticantes de futebol em projetos sociais - Pelicer, Flávio Roberto (2015)
The literature demonstrates important results of sporting activity for young people, both the physical realm as psychic. Objective: To analyze behavior and motivation of young soccer players in social projects. Method: 127 Boys to Age Average 12.93 (+1.46). To assess behavioral profile was used the Child Behavior Checklist for ages 6-18 (CBCL / 6-18) and the Youth Self-Report for ages 11-18 (YSR). Were the data analyzed, compared and segregated into "clinical" and "non-clinical". To assess the motivation for practice was used the “Inventário de Motivação à Prática Regular de Atividade Física e Esportiva” (IMPRAF-54). Results: Among behavioral variables as observed in the Inventories the results indicate that more than 91% of the participants were classified As "No Clinical". As for motivation, the highlighted dimensions were: Health (33.05 + 6.62), Enjoyment (31.99 + 5.78) and Competitiveness (30.92 + 7.01). Conclusion: The data suggest that soccer provides protective mechanisms in relation to the overall psychological functioning of practitioners in the evaluated scales and a greater motivation in health dimensions, pleasure and competitiveness.